A Southeast Asian perspective on the impact of increasingly Autonomous systems on subnational relations of power. Issue 3 (3rd July 2021) - Wyatt, Austin
ABSTRACT: The emergence of increasingly autonomous uninhabited systems has sparked understandable concern among policymakers, defence personnel, and academics, as well as civil-society. Quite reasonably, the body of literature that is arising in response to this concern has largely remained focused on the ethical, legal and practical consequences of "killer robots" being deployed by great power militaries. Unfortunately, however, this has left significant gaps in our understanding of how the diffusion of uninhabited systems and Artificial Intelligence will impact on security of rising middle powers and the lives of their citizens. This article provides an analysis of how the diffusion of uninhabited systems will influence the exercise of sub-national power, using Southeast Asia as its focal point. In other words, this paper asks the question of how autonomous weapon systems will influence the regimes of power and considers how the blurring of the lines between the law enforcement and military use of force paradigms affects law enforcement, border security, and internal surveillance and repression in this region.